2013
DOI: 10.3390/ph6101221
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Central Nervous System Active Drugs During Pregnancy

Abstract: CNS-active drugs are used relatively often during pregnancy. Use during early pregnancy may increase the risk of a congenital malformation; use during the later part of pregnancy may be associated with preterm birth, intrauterine growth disturbances and neonatal morbidity. There is also a possibility that drug exposure can affect brain development with long-term neuropsychological harm as a result. This paper summarizes the literature on such drugs used during pregnancy: opioids, anticonvulsants, drugs used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(154 citation statements)
references
References 159 publications
(164 reference statements)
3
142
3
1
Order By: Relevance
“…Other research on antipsychotic treatment in pregnancy includes pharmacovigilance studies from drug companies' safety databases 76,77 as well as cohort studies based on various data sources. 38,50,[78][79][80][81][82][83][84][85] A systematic review 19 of many of these studies suggested that women requiring antipsychotic treatment during pregnancy have a higher risk of adverse birth outcomes. However, there was substantial heterogeneity between the studies and Coughlin et al 19 emphasise that most studies had limited adjustment for potential confounding and therefore the observed associations may not be causal.…”
Section: Antipsychoticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research on antipsychotic treatment in pregnancy includes pharmacovigilance studies from drug companies' safety databases 76,77 as well as cohort studies based on various data sources. 38,50,[78][79][80][81][82][83][84][85] A systematic review 19 of many of these studies suggested that women requiring antipsychotic treatment during pregnancy have a higher risk of adverse birth outcomes. However, there was substantial heterogeneity between the studies and Coughlin et al 19 emphasise that most studies had limited adjustment for potential confounding and therefore the observed associations may not be causal.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…This has been the subject of a number of recent studies conducted in Europe and North America. [34][35][36][37][38][39][40][41] Epstein et al 39 examined use of psychotropic medication using data from Tennessee Medicaid to conduct a retrospective cohort study of nearly 300,000 women enrolled in the database throughout pregnancy from 1985 to 2005. This study reported significant increases in the use of anticonvulsants among mothers with pain and other psychiatric disorders, but a decrease in the use of lithium and typical antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Mild sedatives (alimemazine, promethazine, propiomazine, and hydroxyzine) were classified separately from the neurotropic drugs.…”
Section: Drug Exposurementioning
confidence: 99%
“…Studija rađena na animalnom uzorku takođe nije našla značajne malformacije u uzorku posle upotrebe diazepama, s tim da je uočeno da plod u ovom uzorki ima manju prosečnu telesnu težinu (animalni uzorci tipično dobijaju veće koncentracije leka u istraživanjima, u ovom slučaku ekvivalent od 240 mg diazepama po kilogramu telesne težine na dan) [10]. Bitno je napomenuti da je starija studija [11] koja je pratila efekte upotrebe diazepama kod trudnica našla povećanu verovatnoću pojave rasepa nepca kod ploda, ali kasnije studije ovo nisu potvrdile, ali su našle (u malom uzorku) češ-ću pojavu atrezije digestivnog trakta [12].…”
Section: Trudnoćaunclassified